Effects of soil compaction, over-top-filling and waterlogging on growth and physiology of Azadirachta excelsa (Jack) Jacobs seedlings - Shukor, Nurul Nasyitah (2014)
Urban forest tree were highly exposed to various type of environmental stress which can give negative effects to their growth. Series of experiments were conducted in investigating the toleration and adaptation of Azadiractha excelsa toward current common stress specifically soil compaction, over-top-filling and waterlogging. Measurement has been made in morphology changes, biomass allocation, root adaptation, and internal physiology comprising chlorophyll fluorescence, gas exchange, hydraulic conductance and water use efficiency. Study was conducted in the nursery of Faculty of Forestry. Repeated measures were used to examine the performance over time of experiment meanwhile one way ANOVA was used to test among different treatments. In soil compaction experiment, soil bulk density of 1.2 g cm-3 (low), 1.4 g cm-3 (medium) and 1.6 g cm-3 (severe) were applied by compacting soil inside the pot. The result showed that severe soil compaction treatments had caused the decrease in physical growth of seedlings. Low optimal value was also found in photochemical efficiency, as well as decreased photosynthetic rate and stomatal conductance. It showed the diligently related root sensitivity of the system architecture to the high mechanical impedance of the soil. However, it still showed capability in tolerance towards compacted soil by maximizing water use a low stomatal conductance in order to have enough sugar to recover stress. Over-top-filling experiment was done by applying a layer of top soil over normal collared seedling. Three different levels of 10 cm, 20 cm and 30 cm had given positively significant results towards performance of the seedling including growth and physiological. Evidently, seedlings in higher soil level had higher relative growth rates in both diameter and height, and also leaf area parameter. It was also found that new areas of root growth were present in higher over-top-filling. There were no significance differences in any parameters of chlorophyll fluorescence, gas exchange and water relations were shown which indicate encourage performance. The third study tested on different periods of time to waterlogged seedling over the 1-week, 2-weeks and 3-weeks duration. Further research was also carried out through moving seedlings out of waterlogged after 2 weeks to assess their recovery. It was found that oxygen deficiency disallow root respiration when it is flooded. Moreover, the ability to allocate more carbon during flooding also appeared to be related to flooding tolerance. A. excelsa seedlings were found are partially tolerance in surviving under compacted soil with declined in morphology performance but still showed some high capability to survive. Instead, it also possesses good morphology and physiology modifications especially in managing photochemical efficiency, gas exchange and water relation which improved their ability to survive in stress condition such over-top-filling and waterlogging conditions. Planting or allowing this seedling to grow in locations where such stresses have the probability to take place is plausible as the trees could still have chance to survive.